NILAI-NILAI PENDIDIKAN MORAL (SANTUN DAN HORMAT PADA ORANG LAIN) DALAM FILM ANIMASI NUSSA DAN RARA (DALAM EPISODE KAK NUSSA) - Medina Nur Asyifah Purnama (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2020)
Amid the rapid development of technology and information accelerate the development of changes in society. Constructive change will bring the condition of a civilized nation, but if the change is destructive then this nation will be increasingly destroyed and possibly become a savage nation. One of these changes is happening in our world of education. Therefore, we must be able to put in mind the character values ​​that form good morals for children. The politeness character is one of the characters that needs to be emphasized together. Children today are very brave towards parents and also teachers. Children dare to threaten their parents and teachers, even in cases of persecution to murder. Sad, when the values ​​of decency finally eroded. As a result children are brutal and wild. How will respect arise if parents, teachers are no longer respected by children? Of course this is a big task for us together to reaffirm the planting of truly upload values, etiquette values, and exemplary values ​​in our environment. The aim is that the culture of respect, respect and the value of courtesy towards others remains entrenched as a manifestation of the noble character of our nation. The cultivation of moral education values ​​must be given to children in interesting ways and in accordance with current technological advancements. For example choosing animated films in which there are Islamic values ​​such as the animation film Nussa, therefore here the researcher wants to find the values ​​in it by using qualitative research methods and data collection techniques using documentation. The results of this study are that the film Nussa and Rara is an animated film that is wrapped in a daily story in the world of children with the delivery of language that is easy to understand, fun and exciting as well as there are instilling of moral values ​​and messages that is to ask people who know better, to call with a good name so that children can behave politely and respect others. Thus the presence of the Nussa and Rara films is expected to help in the moral development of Indonesian children as the Nation's Generation.